2013
DOI: 10.11607/jomi.3099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Implant Surface Roughness on Bacterial Biofilm Formation and Treatment Efficacy

Abstract: A moderately roughened surface did not enhance biofilm formation but reduced treatment efficacy of the biofilms. This finding indicates that efforts should be directed toward optimizing implant surface properties for effective antimicrobial treatment without compromising osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Additionally, a high level of protease activity may be a predictive factor for disease progression in peri-implantitis [38]. Rougher implant surfaces were found to cause reduced treatment efficacy, for example in the treatment of biofilm by chlorhexidine, but no influence on the amount of biofilm formation [54].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a high level of protease activity may be a predictive factor for disease progression in peri-implantitis [38]. Rougher implant surfaces were found to cause reduced treatment efficacy, for example in the treatment of biofilm by chlorhexidine, but no influence on the amount of biofilm formation [54].…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of this biofilm with previously published investigations evaluating biofilm formation on implant surfaces is difficult since these studies have used different samples such as disks, squares, nanotubes, etc, but not whole implant surfaces depicting the typical macro-structural design characteristics of threads, picks, and valleys (B. Guggenheim, Giertsen, Schupbach, & Shapiro, 2001;Lin et al, 2013;Narendrakumar et al, 2015;Park, Lee, Um, Chang, & Lee, 2014;Rath, Stumpp, & Stiesch, 2017;Roehling et al, 2017;Sanchez et al, 2014;Schmidlin et al, 2013;Thurnheer & Belibasakis, 2016;Violant et al, 2014). Similarly to the morphology shown on titanium and zirconium disks using the same multispecies bacterial inoculum (Sanchez et al, 2014), the resulting biofilms formed a continuous dense mass, covering the entire surface of the implant surface.…”
Section: Lower Limit Upper Limitmentioning
confidence: 99%
“…These complex surface topographies, which clearly enhance implant osseointegration, may also facilitate the development of complex biofilms and impair their cleanability (Ferreira Ribeiro et al, 2016;Di Giulio et al, 2016;Song, Koo, & Ren, 2015;Violant, Galofre, Nart, & Teles, 2014;Xing, Lyngstadaas, Ellingsen, Taxt-Lamolle, & Haugen, 2015). Previous in vitro research on implant surfaces has shown that roughness, surface free energy, wettability, and degree of sterilization may affect biofilm formation, bacterial three-dimensional distribution, and antimicrobial treatment efficacy (Al-Ahmad et al, 2010;Di Giulio et al, 2016;Lin, Liu, Wismeijer, Crielaard, & Deng, 2013;Schmidlin et al, 2013;Song et al, 2015;Yeo, Kim, Lim, & Han, 2012). These studies have used specimens, such as disks or slabs containing the studied surface (Aguayo, Donos, Spratt, & Bozec, 2015;de Avila et al, 2015;Di Giulio et al, 2016;Papavasileiou, Behr, Gosau, Gerlach, & Buergers, 2015;Pita et al, 2015;Ready et al, 2015), but these specimens lack the macro-structural and topographic characteristics of the dental implants used clinical practice.…”
mentioning
confidence: 99%
“…It involved the nucleation and formation of bone-like crystals on a pretreated substratum by immersing it in a supersaturated solution of CaP under physiological conditions of temperature (37°C) and pH (7.4). The method has been improved and refined by several groups of researchers [ 9 , 11 , 18 - 20 ], and an extensive evaluation as well as pre-clinical studies have been made [ 21 , 22 ]. Recently a biomimetic calcium phosphate bone substitute has been developed based on biomimetic calcium phosphate coating [ 23 , 24 ].…”
Section: Biomimetic Calcium Phosphate Coatingsmentioning
confidence: 99%